Monoclonal gammopathy with systemic amylodosis: an evaluation of diagnostic elements - Chellappah Thambiah, Subashini; George, Elizabeth; Umar, Nor Aini (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2011)
Monoclonal gammopathies result from an overproduction of a single abnormal clone of plasma cell or B lymphocyte that produce an immunologically homogenous immunoglobulin (Ig) commonly referred to as paraprotein or monoclonal (M) protein. The circulating M-protein may consist of an intact immunoglobulin, the light chain only, or (rarely) the heavy chain only. The heavy chain is from one of the five immunoglobulin classes G, A, M, D or E, while the light chain is either kappa (κ) or lambda (λ) in type. Accurate detection and quantitation of monoclonal immunoglobulins is important for the diagnosis and management of monoclonal gammopathies. We report a case of a 71 year old lady with a history of chronic gastritis and recurrent lower respiratory tract infection whereby no specific diagnosis was made until a computed tomography (CT) guided lung biopsy and orogastroduodenoscopy.